Polyetheretherketone (PEEK) in Oral Rehabilitation of Sarcopenic Patients: A Muscle-Preserving Prosthodontic Approach - Sowmya, Srinivas; Nagesh, NagaUsha; Mysore, Nanditha Kumar (International Journal of Dental Materials, 2025)
Sarcopenia, a progressive decline in skeletal muscle mass and function, has profound implications for oral health, reducing masticatory strength, adaptation to prostheses, and nutritional intake. Polyetheretherketone (PEEK) is a high-performance polymer with favourable biomechanical, biocompatible, and digital-workflow properties. Although PEEK is increasingly used in prosthodontics, its role in preserving or enhancing orofacial muscle function in sarcopenic patients has not been systematically explored. This manuscript reviews the advantages of PEEK over traditional materials, analyses its biomechanical relevance to sarcopenia, and proposes a clinical rationale for adopting PEEK as a therapeutic material in this context. The discussion evaluates current evidence of PEEK’s application in dentures, frameworks, and implant prostheses, noting its potential to reduce muscular load, cushion occlusal forces, and improve patient comfort. Finally, this manuscript calls for targeted clinical trials focusing on sarcopenic populations to validate PEEK’s long-term efficacy in mitigating oral frailty and promoting healthy aging.